2013
DOI: 10.1186/1755-7682-6-36
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of prostatic lesions

Abstract: BackgroundProstate gland of male reproductive system is about the size of walnut and surrounds the urethra. Most frequently encountered diseases affecting prostate are Prostatitis, Benign prostatic hyperplasia and Prostatic cancer .Our objective of study was to evaluate the spectrum and correlation of prostatic lesions with presenting complaints of patient.MethodsIt was a cross-sectional study conducted in Pathology Department of Dow Medical College, Dow University of Health Sciences during the period of 1st J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 5 publications
6
15
1
Order By: Relevance
“…11 Basal cell hyperplasia was the other significant co-existing histopathological finding (4.15%). Basal cell hyperplasia was reported as coexistent finding in (5.4%) of cases Mittal et al and (3.85%) by monika et al 10,11 Two cases of granulomatous prostatitis negative for AFB were also seen and reported as nonspecific granulomatous prostatitis. Cribriform hyperplasia and squamous metaplasia were the other but less frequent histopathological findings.…”
Section: Discussionmentioning
confidence: 93%
“…11 Basal cell hyperplasia was the other significant co-existing histopathological finding (4.15%). Basal cell hyperplasia was reported as coexistent finding in (5.4%) of cases Mittal et al and (3.85%) by monika et al 10,11 Two cases of granulomatous prostatitis negative for AFB were also seen and reported as nonspecific granulomatous prostatitis. Cribriform hyperplasia and squamous metaplasia were the other but less frequent histopathological findings.…”
Section: Discussionmentioning
confidence: 93%
“…Our study not only provides a plausible clue as to how the cytostatic TGFβ pathway may be switched to pro‐tumorigenic mode by transcriptional and post‐translational dysregulation of certain TGFβ components, it also showed that the molecular pattern of TGFβ signaling is remarkably distinct in prostate cancer and BPH in spite of their commonalities with respect to risk factors, pathological drivers and symptoms. This is a novel and clinically useful finding since BPH is the most common non‐malignant lesion of prostate gland that often coexists with prostate cancer in aged men (Aslam et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The common age group involved in this series was 50-60 and 60-70 years as was ascertained in other studies. 3,13 Many literatures are present of studies in India and abroad diagnosing BNH as the highest percentage of cases. Outcome of some studies are similar to our findings of 73.91%.…”
Section: Discussionmentioning
confidence: 99%